ANALISIS WARNA CAHAYA LAMPU TERHADAP HASIL TANGKAPAN IKAN - Loupatty, Grace (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2012)
By learning and researching the wave-length of light and its propagation we can make an observation of the function and effectiveness light as a stimulation in fishing.The purposes of the observation are: to know how the color of light lamp influences to the result of fishing; to observe how the depth of location for fishing influences the reduction of light intensity; to know what is the relation between parameter condition/ atmosphere (salinity, temperature and transparency of the water) with the result of fishing.The observation is applied with a direct observation method in water of Batu Dua- Ambon Island.The total result of fishing is 57.2 kilograms with applied for us different light lamp (red, yellow, green and blue). Each color applied has the result: the red light lamps got amount of 4.5 kg; the yellow light lamps got amount of 15,1 kg ; the green light lamps got amount 17.4 kg; and the blue light lamps got amount of 20.2 kg.Data analysis statistically using an analysis of variance system which indicates that the stimulation light lamp influences to the result of fishing.Result of the statistical observation shows that parameter conditions/ atmosphere in the water, such as salinity. temperature, transparency of the water, such as: salinity, temperature, transparency of the water do not influence to the result of fishing.